Sanitary, physiological quality and alternative treatments of Dimorphandra gardneriana Tul. seeds - Flávio Ricardo da Silva Cruz; Rosemere dos Santos Silva; Maria das Graças Rodrigues do Nascimento; Demetrius José da Silva; Luciana Cordeiro do Nascimento (Bioscience Journal, 2018)
The Dimorphandra gardneriana Tul. species is widely distributed in the Brazilian territory presenting an economic and environmental importance. The aim of this study was to determine the fungi associated with Dimorphandra gardneriana seeds, assessing the influence of nystatin, the castor oil plant and Captan® fungicide in the control of these fungi in the seed germination and seedlings growth. The experiment was carried out at the Laboratório de Fitopatologia and Análise de Sementes of the Departamento de Fitotecnia e Ciências Ambientais of Centro de Ciências Agrárias of the Universidade Federal da Paraíba, Areia-PB, Brazil. Ten treatments were applied for mycoflora control: T1 - control (untreated seeds); T2 - nystatin (0.1%); T3 - nystatin (0.2%); T4 - nystatin (0.3%); T5 - nystatin (0.4%); T6 - castor bean oil (0.25%); T7 - castor bean oil (0.5%); T8 - castor bean oil (0.75%); T9 - castor bean oil (1%); T10 - fungicide Captan®. For the evaluation of the effect of the treatments on the Dimorphandra gardneriana seeds the following variables were evaluated: germination, first counting of germination and germination speed index, percentage of abnormal seedlings, length and dry matter of shoots and roots of seedlings. Nystatin (0.1%) reduced the incidence of Aspergillus sp. The Captan® fungicide reduced the incidence of fungi in the seeds and provided the best results for germination and vigor.